PEER ROLE IN THE FORMING STUDENTS’ MORAL BEHAVIOR CLASS VI SDN SUDIMARA TIMUR 2 - Yandani, Nur; Tiurlina, Tiurlina; Alfarisa, Fitri (Didaktika, 2022)
Moral values are a significant aspect that needs to be implanted in education in schools. The process of inculcating this value is often associated with the environment in which students are located. One of the locations where students waste the most time is with their peers. This research is a qualitative descriptive research with a case study method. Data collection techniques in this study were observation, interviews, and documentation. The participants in this study were 30 students in sixth grade at The State Elementary School of Sudimara Timur 2. This research was conducted by observing the behavior of students related to good behavior in accordance with the moral values of their peers. The results of this study are as follows: (1) There are several roles given by students in the process of forming moral behavior, namely first as a model or example in the imitation process that students use to their peers, second as a source of support, both ego support and physical support, third as friends or friends, where in terms of forming the moral behavior of students as friends they remind each other good and bad things to other peers, fourth as forming various moral behaviors. (2) the efforts made by teachers in implementing moral education in accordance with the humanist education approach in schools based on expert theory, which in this approach is carried out to educate students to have good moral behavior. There are four approaches, namely inclusion, modeling, value facilitation, and skills development.